Studi Tafsir Maudhu’i tentang Konsep Hisab dalam Al-Qur’an - Sadad Mujahid; Dadan Rusmana (Gunung Djati Conference Series, 2022)
This study aims to discuss the concept of the word hisab in the Qur'an. This research method uses qualitative research through a literature study approach and thematic interpretation methods. The results and discussion of this study are the word hisab is mentioned 42 times in the Qur'an with various forms of its derivation, there is also a synonym for this hisab, namely the word hasib which is mentioned 12 times in the Qur'an with various derivations. This study concludes that the word reckoning is often juxtaposed with Allah's calculations which are certain to be true. The word hasib which means an estimate is often juxtaposed with humans who are not sure what will happen, even far from being true. Allah's calculations are also divided into three categories, namely the calculation of time, sustenance, and charity. Then man's prediction is that people who have sinned will not be tormented, will not be tested, those who want to enter heaven, will not return to Allah after he dies. This study recommends that research be conducted on other hisab in the Qur'an.